PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI KONSELOR DALAM MENINGKATKAN MINAT BELAJAR SISWA - Nurul Insani Putri Aulia; Nuruddin Araniri (Al-Mau'izhoh, 2021)
Based on the preliminary study that the author did, it turns out that the role of Islamic Religious Education teachers as counselors has not been optimal. This can be seen from the symptoms experienced by Islamic Religious Education Teachers. Among them are some teachers of Islamic Religious Education who allow students' learning problems, do not help students who have learning difficulties, do not reprimand students who violate discipline, do not know and understand students well and do not provide information on the condition of students to parents. This study aims to find out how the role of Islamic Religious Education Teachers as counselors and what are the efforts of Islamic Religious Education Teachers to provide counseling services in increasing student interest in learning at SDN Gandu I. The type of research used in this study is qualitative research using qualitative descriptive methods. . The data collection used is by conducting observations, interviews and documentation. The results showed that the role of PAI teachers as counselors were: as listeners, helping students overcome learning problems, as motivators and giving reprimands. While the efforts made by PAI teachers in increasing student interest in learning are by: creating a pleasant learning atmosphere, paying more attention, using varied learning methods and media and being good role models.